(untitled) (Journal of Innovative Research, 2024)
The study assessed the profit efficiency and the responsible factors for the inefficiency of dairy farmers in West Shewa milkshed, central Ethiopia. A multistage random sampling method was employed to select sample households. The primary data were collected using structured questionnaires with computer-assisted personal interviews (CAPI). Descriptive and econometric data analysis were performed, and the stochastic frontier model was the model used. The result disclosed that the dairy business is profitable, and the mean efficiency score is 71%, indicating the existence of 29% inefficiency in dairy farming. This result indicates that enhancement of all the efficiencies will enable households to attain a potential profit of 88428.25 birrs. Sex, the price of milk, and the number of cows owned were the main factors that affected the profit inefficiency of the dairy farmers. This study suggests that the profit efficiency of dairy farmers will be enhanced if they choose their dairy farm sizes based on the production resources they have, and if the milk collection centers are availed in all villages.